Intracranial Administration of P Gene siRNA Protects Mice from Lethal Chandipura Virus Encephalitis - Kumar, Satyendra (Public Library of Science, 2010)
BACKGROUND: In parts of India, Chandipura Virus (CHPV) has emerged as an encephalitis causing pathogen in both epidemic and sporadic forms. This pediatric disease follows rapid course leading to 55–75% mortality. In the absence of specific treatment, effectiveness of RNA interference (RNAi) was evaluated. METHODS AND FINDINGS: Efficacy of synthetic short interfering RNA (siRNA) or short hairpin RNA (shRNA) in protecting mice from CHPV infection was assessed. The target genes were P and M genes primarily because important role of the former in viral replication and lethal nature of the latter. Real time one step RT-PCR and plaque assay were used for the assessment of gene silencing. Using pAcGFP1N1-CHPV-P, we showed that P-2 siRNA was most efficient in reducing the expression of P gene in-vitro. Both quantitative assays documented 2logs reduction in the virus titer when P-2, M-5 or M-6 siRNAs were transfected 2hr post infection (PI). Use of these siRNAs in combination did not result in enhanced efficiency. P-2 siRNA was found to tolerate four mismatches in the center. As compared to five different shRNAs, P-2 siRNA was most effective in inhibiting CHPV replication. An extended survival was noted when mice infected intracranially with 100 LD(50) CHPV were treated with cationic lipid complexed 5 µg P-2 siRNA simultaneously. Infection with 10LD(50) and treatment with two doses of siRNA first, simultaneously and second 24 hr PI, resulted in 70% survival. Surviving mice showed 4logs less CHPV titers in brain without histopathological changes or antibody response. Gene expression profiles of P-2 siRNA treated mice showed no interferon response. First dose of siRNA at 2hr or 4hr PI with second dose at 24hr resulted in 40% and 20% survival respectively suggesting potential application in therapy. CONCLUSIONS: The results highlight therapeutic potential of siRNA in treating rapid and fatal Chandipura encephalitis.